A study of urgent and emergency referrals from NHS Direct within England. Issue 5 (11th May 2015) - Cook, E J; Randhawa, G; Guppy, A; Large, S
Abstract : Objectives: The presented study aimed to explore referral patterns of National Health Service (NHS) Direct to determine how patients engage with telephone-based healthcare and how telephone-based healthcare can manage urgent and emergency care. Setting: NHS Direct, England, UK Participants: NHS Direct anonymised call data (N=1 415 472) were extracted over a representative 1-year period, during the combined month periods of July 2010, October 2010, January 2011 and April 2011. Urgent and emergency calls (N=269 558; 19.0%) were analysed by call factors and patient characteristics alongside symptom classification. Categorical data were analysed using the χ 2 test of independence with cross-tabulations used to test within-group differences. Primary and secondary outcome measures: Urgent and emergency referrals to 999; accident and emergency or to see a general practitioner urgently, which are expressed as call rate per 100 persons per annum. Outcomes related to symptom variations by patient characteristics (age, gender, ethnicity and deprivation) alongside differences by patient characteristics of call factors (date and time of day). Results: Urgent and emergency referrals varied by a range of factors relating to call, patient and symptom characteristics. For young children (0–4), symptoms related to 'crying' and 'colds and flu' and 'body temperature change' represented the significantly highest referrals to 'urgent and emergency' health services symptoms relating to 'mental health' alongside 'pain' and 'sensation disorders' represented the highest referrals to urgent and emergency health services for adults aged 40+ years. Conclusions: This study has highlighted characteristics of 'higher likelihood' referrals to urgent and emergency care through the delivery of a national nurse-led telephone healthcare service. This research can help facilitate an understanding of how patients engage with both in and out of hours care and the role of telephone-based healthcare within the care pathway.